Good vibrations : my life as a Beach Boy - Love, Mike, 1941-; Hirsch, James S. (Blue Rider Press, 2016)
Mike Love tells the story of his legendary, raucous, and ultimately triumphant five-decade career as the front man of The Beach Boys, the most popular American band in history -- timed to coincide with the 50th anniversary of "Good Vibrations." Love describes the stories behind his lyrics for pop classics such as "Good Vibrations," "California Girls," "Surfin' USA," and "Kokomo," while providing vivid portraits of the turbulent lives of his three gifted cousins, Brian, Dennis, and Carl Wilson. His partnership with Brian has few equals in American pop music, though Mike has carved out a legacy of his own -- he co-wrote the lyrics to eleven of the twelve original Beach Boy songs that were top 10 hits while providing the lead vocals on ten of them.